La influencia del apoyo socio afectivo del docente en el desarrollo de la lectoescritura en niños de ciclo I (2022)
The present research was approached from the relationship between the socioaffective support of the teacher and the literacy development, for which the articles that meet this criterion, published between 2014 and 2021, were identified to provide various discursive segments that allow to demonstrate the theoretical characterization in relation to the emotion of the teacher, the conceptual and methodological continuities and ruptures between the various existing approaches, as well as the socio-affective and didactic resources used as a determining factor for the development of literacy. The methodology is qualitative, with a descriptive documentary study design in a step-by-step process, whose results reflected the existing relationships between teaching methods and work models, as the main ways of working on socio-affectivity in cycle I, in order to promote the teacher's role in the stimulation of the zone of proximal development (ZDP) from early childhood.